Application of the Black-Litterman model (BL) with optimization on the Philippine Stock Exchange index (PSEi) from 2013 to 2019 - Navarro, Carlos Roberto Q. (Animo Repository, 2020)
The BL model is a great jump from traditional optimization models because it provides a more realistic model in the field of portfolio management. By incorporating a market equilibrium and investor views, the BL model addressed most of the weaknesses of other optimization models. While not perfect, the author has found this to be the best model out there in the field in terms of applicability, robustness, and stability. Since the author found no published thesis or paper applying the BL model to the Philippines, it is the aim of this study to be the first formal paper applying the BL model in the Philippine Stock Exchange. Since the model is relatively new compared to the Modern Portfolio Theory, the author hopes to add this paper to the current literature regarding the Black- Litterman model. This study will also help determine the applicability of the BL model in Emerging Markets such as the Philippines. By determining this, the author can confidently say that the BL model has worldwide applicability regardless of the complexity of the country’s financial market. Lastly, the author aims to apply everything that was learned in the Master of Science in Computational Finance. This thesis is the culmination and final application of all topics learned by the researcher in this degree. This thesis hopes to cross the border from theory to practice by finally applying a novel concept in the real world of Portfolio Management.